BIOCONVERSION OF CORN GRAIN COMPOUNDS TO OBTAIN BIOETHANOL - Khomichak, Volodymyr; Kuznіetsova Inha; Oliynychuk, Sergii; Koval, Olga (Science-based technologies, 2026)
The paper shows that starch-containing raw materials are one of the promising types of raw materials for bioethanol production due to the high conversion rate and yield of bioethanol. Currently, leading countries in the world are switching to the use of bioethanol and also use non-traditional raw materials for its production. Ukraine, due to agro-climatic conditions, is rich in the production of starch-containing raw materials. A significant proportion of grain raw materials is substandard (for example, substandard corn grain) and is not use for food purposes. Such raw materials are promising starch-containing raw materials for processing into bioethanol. Intensification of alcohol production has a number of technological solutions aimed at increasing the yield of alcohol, one of which is proteolysis. Many scientific studies have been devoted to the study of the issue of proteolysis, while the use of modern commercial enzyme preparations requires further development of this area. The studies used modern drugs that are common at alcohol enterprises. Studies have shown that the action of the proteolytic enzyme preparation softens the structure of the starch-protein matrix and intensifies its destruction during heating. This allows you to adjust the mash dilution mode by using proteolytic and amylolytic enzyme preparations, reduces the viscosity of the mash, reducing its value by 60.4%, compared to the mash in which there is no enzyme preparation. The use of proteolysis during saccharification contributed to the intensive accumulation of sugars, the reason for which is the synergism of the action of protease and glucoamylase preparations. It established that the quality indicators of the matured mash show the effectiveness of the use of the proteolytic enzyme preparation during the dilution of corn mash. In addition, adjusting the process of bioconversion of corn raw materials and significantly shorten the saccharification process. It has been proven that proteolysis improves the saccharification process and provides the wort with easily digestible nitrogen nutrition, the yeast generation process and increases the alcohol yield by 0.4 dal/t of raw material.